A NOVEL TECHNIQUE FOR EXTRACTION OF DROPPED BROKEN HAPTICS OF HARD POSTERIOR CHAMBER INTRAOCULAR LENS. Issue Volume 15:Issues 1(2021) (2021) - Elwan, Mohamed Mamdouh
Abstract : Background/Purpose: To report a novel technique for extraction of dropped haptics of hard posterior chamber intraocular lens. Methods: A 58-year-old woman had undergone cataract extraction, and while implanting the posterior chamber intraocular lens it was dislocated in the anterior vitreous, and the cataract surgeon, tried to remove it by the anterior approach, but he succeeded to remove the optic part only, leaving the haptics dropped, then he referred the case after giving topical and systemic medications to control intraocular inflammation and, the case was prepared for pars plana vitrectomy, then injection of perfluorodecaline to keep the haptics away from the posterior pole then by 23 G vitrectomy probe and, the use of vacuum only, the haptics were removed and the perfluorodecaline was removed. Results: After extraction of both haptics by 23 G vitrectomy probe, the case was implanted by a hard polymethylmethacrylate posterior chamber intraocular lens on the sulcus, and postoperatively, the inflammatory signs were subsided and her visual acuity was improved, without any posterior segment complications. Conclusion: Dropped haptic of hard posterior chamber intraocular lens can be removed successfully with 23 G vitrectomy probe. Abstract : Supplemental Digital Content is Available in the Text.A 58-year-old woman had performed cataract extraction, but unfortunately, the posterior chamber intraocular lens dropped and the haptics had been broken while trying to remove it from the anterior vitreous by the anterior segment surgeon; 1 month later, the case was referred and had performed vitrectomy and extraction of both haptics by 23 G vitrectomy probe.